Polyphony in Dostoevsky’s Novels and the Multiplicity of Voices in Norwid’s Poetry - Skalińska, Ewangelina (Colloquia Litteraria, 2018)
The article compares dominating strategies of writing in Norwid’s and Dostoyevsky’s literary output. The author presents the sources of the conversational concepts in the writings of both Norwid and Dostoyevsky. She also reflects upon the origins of the indicated affinity.